Sistem Informasi Penelitian dan Pengabdian Masyarakat pada LPPM Universitas Timor - Claria Berek; Septian S. Manek (Fakultas Pertanian, Universitas Timor, 2019)
Information technology consists of computers to process data, network systems to connect computers, and communication technology for distribution of data for global access.Now, the University of Timor has no information system to manage the data collection of research reports and lecturers' community service. This situation makes the data collection of reports in the LPPM section not yet effective.Data processing at the University of Timor LPPM is still manual, in the form of recording on paper and files on a computer. Even though the data collection already uses a computer, the data stored is irregular and not centralized.Based on the above problems, we created a system to assist the process of data collection of research reports and community service lecturers at the University of Timor LPPM, we used Adobe Dreamweaver CS5.The test results show that after implementing our system at LPPM, the research and service data becomes well organized in one database, it is more effective and efficient in managing data and information about LPPM activities.